Sperm FISH analysis of a 44, X, der(Y), t(Y;15)(q12;q10)pat, rob(13;14)(q10;q10)mat complex chromosome rearrangement. (22nd May 2013) - Ferfouri, F.; Boitrelle, F.; Clement, P.; Molina Gomes, D.; Selva, J.; Vialard, F.
Summary Complex chromosome rearrangements (CCR) with two independent chromosome rearrangements are rare. Although CCRs lead to high unbalanced gamete rates, data on meiotic segregation in this context are scarce. A male patient was referred to our clinic as part of a family screening programme prompted by the observation of a 44, X, der(Y), t(Y;15)(q12;q10)pat, rob(13;14)(q10;q10)mat karyotype in his brother. Karyotyping identified the same CCR. Sperm FISH (with locus‐specific probes for the segments involved in the translocations and nine chromosomes not involved in both rearrangements) was used to investigate the rearrangements meiotic segregation products and establish whether or not an inter‐chromosomal effect was present. Sperm nuclear DNA fragmentation was also evaluated. For rob(13;14) and der(Y), the proportions of unbalanced products were, respectively, 26.4% and 60.6%. Overall, 70.3% of the meiotic segregation products were unbalanced. No evidence of an inter‐chromosomal effect was found, and the sperm nuclear DNA fragmentation rate was similar to our laboratory's normal cut‐off value. In view of previously published sperm FISH analyses of Robertsonian translocations (and even though the mechanism is still unknown), we hypothesise that cosegregation of der(Y) and rob(13;14) could modify rob(13;14) meiotic segregation.